2013
DOI: 10.2134/agronj2013.0089
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Red Clover Nitrogen Credit to Corn: Evaluating Cover Crop Introduction

Abstract: Corn (Zea mays L.) production systems can benefit from introducing a leguminous winter cover crop into the rotation, especially with regard to increased N availability (i.e., legume N credit); however, it is not known if the full agronomic benefit is realized in the first year of cover crop introduction or if the benefit is cumulative with time. The objective of this study was to determine the apparent red clover (Trifolium pratense L.) N credit to corn in a conventional system where red clover was introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 43 publications
5
37
0
Order By: Relevance
“…Spring and fall biomass values of RC in the current study were 4059 and 6796 kg ha −1 , which were greater than the values reported for RC (734–3140 kg ha −1 ) from a similar soil within ∼90 km of this field site (Coombs et al, 2017) as well as greater than the 690 to 4200 kg ha −1 reported in temperate climates (Snapp et al, 2005; Gaudin et al (2013, 2014). Coombs et al (2017) noted that when RC was left alive over winter, biomass was increased relative to the fall biomass in Ontario (Vyn et al, 2000; Gaudin et al, 2013; Thilakarathna et al, 2015) as well as in Ohio and Michigan (Henry et al, 2010; Gentry et al, 2013). Over winter increase of RC biomass also occurred in this study with the average biomass of 4059 kg ha −1 in the fall increasing to 6796 kg ha −1 in the following spring.…”
Section: Resultsmentioning
confidence: 99%
“…Spring and fall biomass values of RC in the current study were 4059 and 6796 kg ha −1 , which were greater than the values reported for RC (734–3140 kg ha −1 ) from a similar soil within ∼90 km of this field site (Coombs et al, 2017) as well as greater than the 690 to 4200 kg ha −1 reported in temperate climates (Snapp et al, 2005; Gaudin et al (2013, 2014). Coombs et al (2017) noted that when RC was left alive over winter, biomass was increased relative to the fall biomass in Ontario (Vyn et al, 2000; Gaudin et al, 2013; Thilakarathna et al, 2015) as well as in Ohio and Michigan (Henry et al, 2010; Gentry et al, 2013). Over winter increase of RC biomass also occurred in this study with the average biomass of 4059 kg ha −1 in the fall increasing to 6796 kg ha −1 in the following spring.…”
Section: Resultsmentioning
confidence: 99%
“…Corn N biomass (109.1-148.1 kg ha −1 ) and grain yield (5800-7200 kg ha −1 ) were increased by including red clover when compared to fallow [26]. Nitrogen credit from red clover (30-48 kg N ha −1 ) was similar across management type with the first year of introduction to the conventional system providing an apparent 55 kg N ha −1 [27]. Relay-cropping increased the average return to N investments across the N fertility gradient when estimating N and forage values of red clover biomass (265-1380 kg ha −1 ) compared to wheat [28].…”
Section: Introductionmentioning
confidence: 99%
“…Corn is often planted following a red clover cover crop to utilize available N. Several researchers have shown greater corn N uptake and/or yield following a clover cover crop compared with no cover (Torbert and Reeves, 1991; Dapaah and Vyn, 1998; Vyn et al, 2000; Gentry et al, 2013). One season of clover increased residual soil inorganic N for at least 2 yr following incorporation compared with synthetic N (Harris et al, 1994).…”
mentioning
confidence: 99%
“…One season of clover increased residual soil inorganic N for at least 2 yr following incorporation compared with synthetic N (Harris et al, 1994). However, a long‐term clover stand did not have an additive effect on soil N compared with a single season of red clover planted as a cover crop (Gentry et al, 2013).…”
mentioning
confidence: 99%